Forum sobre bosques, gestion y desarollo: opciones para la Amazonia - Pokorny, B.; Sabogal, C.; Kramer, F. (Center for International Forestry Research, 2004)
The Brazilian government's initiative to systematically search for the eradication of hunger in Brazil by means of the Fome Zero Program has aroused global interest and sympathy. In the search for efficient strategies to reach this objective, the situation in Amazonia deserves special attention. Either of the precarious conditions of its health care, education and economic situation, under which a great part of the rural population lives, as well as for the existence of extensive areas of forests which are characterized by a huge diversity of timber and non-timber forestry products. In the discussion on the possible contributions of forest towards development, there are quite opposed positions: some believe that forests are an obstacle while others see them as the engine of development. In order to present and discuss the various proposals and visions on the role of forests in the fight against poverty and to promote the sustainable development of the Amazon region, CIFOR, together with its partners - EMBRAPA, GTZ, PROMANEJO/IBAMA and IMAZON- held a forum under the title "Forest Management and Development: Options for Amazonia" The events gave an opportunity for researchers, experts on rural development initiatives and also politicians involved in the issue to present and discuss the various proposals on the theme. This book contains the 13 papers presented during the forum and a video-CD with a compilation of the debate that followed, as a contribution in the search of the best solutions for sustainable development of the region.